Anti-Corruption Education Model with a Legal Harmonization Approach to Strengthen the National Legal System - rezi, rezi; Saputro, M Susilo Agung (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Corruption is one of the main issues that hinder national development and weaken the legal system in Indonesia. Anti-corruption education serves as an effective preventive strategy by instilling the values of honesty, integrity, and legal awareness from an early age. The legal harmonization approach in anti-corruption education aims to create a more integrated, coherent, and effective legal system in combating corruption. Through legal harmonization, regulations related to corruption eradication can be aligned to reduce overlapping rules and enhance the effectiveness of law enforcement. This legal harmonization-based anti-corruption education model is expected to strengthen the national legal system and foster a stronger legal culture within society. This study employs a qualitative method with a literature review approach to analyze the relevance of legal harmonization in anti-corruption education and its impact on the national legal system. The research findings indicate that anti-corruption education based on legal harmonization can improve public understanding of the legal system, encourage active participation in public policy oversight, and reinforce government transparency and accountability.